Association of maternal serum cadmium level during pregnancy with risk of preterm birth in a Chinese population. (September 2016) - Wang, Hua; Liu, Lu; Hu, Yong-Fang; Hao, Jia-Hu; Chen, Yuan-Hua; Su, Pu-Yu; Yu, Zhen; Fu, Lin; Tao, Fang-Biao; Xu, De-Xiang
Abstract: Cadmium (Cd) was a developmental toxicant that induces fetal malformation and growth restriction in mice. However, epidemiological studies about the association of maternal serum Cd level with risk of preterm birth were limited. This study was to investigate whether maternal serum Cd level during pregnancy is associated with risk of preterm birth in a Chinese population. Total 3254 eligible mother-and-singleton-offspring pairs were recruited. Maternal serum Cd level was measured by GFAAS. Based on tertiles, maternal serum Cd concentration was classified as low (LCd, <0.65 μg/L), medium (MCd, 0.65–0.94 μg/L) and high (HCd, ≥0.95 μg/L). Odds ratio ( OR ) for preterm birth was estimated using multiple logistic regression models. Results showed the rate of preterm birth among LCd, M-Cd and HCd was 3.5%, 3.8%, and 9.4%, respectively. Subjects with HCd had a significantly higher risk for preterm birth ( OR : 2.86; 95% CI : 1.95, 4.19; P  < 0.001) than did those with LCd. Adjusted OR for preterm birth was 3.02 (95% CI : 2.02, 4.50; P  < 0.001) among subjects with HCd compared to subjects with LCd. Taken together, the above results suggest that maternal serum Cd level during pregnancy is positively associated with risk of preterm birth. Graphical abstract: Highlights: Maternal serum Cd level during pregnancy is positively associated with risk of preterm birth. Maternal serum Cd level during pregnancy is positively associated with risks of moderate and late preterm births. Maternal serum Cd level at early or middle gestational stages is positively associated with risk of preterm birth. Abstract : Maternal serum Cd level during pregnancy is positively associated with risk of preterm birth.